CLONING AND EXPRESSION ANALYSIS OF BETA-ISOPROPYLMALATE DEHYDROGENASE FROM POTATO - Sonnewald, Uwe; et al. (Molecular and General Genetics MGG, 1993)
A full-length cDNA clone for beta-isopropylmalate dehydrogenase from potato has been isolated and sequenced. The open reading frame is 1071 bp in length encoding a protein of 357 amino acids which includes a 29 amino acid, putative chloroplastic transit peptide. The amino acid sequence shows 33.3 % and 28.6 % identity to beta-isopropylmalate dehydrogenases from rape and Bacillus subtilis, respectively. Southern analysis shows that the gene is present in low copy number in potato, and in single copy in tomato and Arabidopsis. The gene is expressed in all tissues of the potato plant and its expression is increased by leucine, and leucine plus threonine, in contrast to the situation in yeast and prokaryotes. The gene is also induced by sucrose in a manner similar to that seen with genes involved in carbohydrate metabolism, which indicates that there may be some interaction at the transcriptional level between genes involved in carbon and nitrogen metabolism.
Keywords: BETA-ISOPROPYLMALATE DEHYDROGENASE; LEUCINE